‘We both just wanted to be normal parents’: a qualitative study of the experience of maternity care for women with learning disability - Malouf, Reem; McLeish, Jenny; Ryan, Sara; Gray, Ron; Redshaw, Maggie (BMJ open, 2017)
BackgroundMore women with learning disability (LD) are becoming mothers. Women with LD have rights to equal access to maternity care that meets their needs, however, many have poor pregnancy and birth outcomes compared to other women in the UK. Research is limited in this area.ObjectivesThe aim of the study was to explore the lived experiences of pregnancy, childbirth, prenatal and postnatal care and services received by this group of women in the UK, including their expressed information and support needs relating to maternity care.MethodsA qualitative study in which data were generated using in-depth semistructured interviews with learning disabled women who were pregnant or had given birth within the last 3 years in the UK; data were analysed using interpretative phenomenological analysis.Results9 women with varying levels of cognitive impairment took part. 4 super-ordinate themes were identified: ‘I hate being treated differently’, ‘I find it harder to understand than other people’, ‘We've had to prove ourselves’ and ‘Make sure you've got very good support around you’. Subthemes included: ‘Negative attitudes and denial of choice’, ‘Understanding of normal care’, ‘Written information’ and ‘Being judged by professionals’.ConclusionsWith support from family and services, learning disabled women can become confident and successful parents. Maternity services should make reasonable adjustments when providing care to this group, including adapting to their individual communication and learning needs: allowing sufficient time in appointments, offering clear explanations of each aspect of care and sensitive support for autonomy and fully informed choice. Mothers who will be subject to a social care assessment of their parenting skills need clear information about the process, their choices and the level of skill they must demonstrate, as well as access to sufficient antenatal and postnatal support to give them the best possible chance of passing the assessment.